Protecting children from domestic violence A comparative study of Iraqi laws - حسين شذى مظفر (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The family is considered the nucleus that supports society with new members through its formation of children and their correct upbringing. Childhood is one of the most important stages of a person’s life and has a great impact on preparing and developing his personality. It was and still is the focus of attention of laws and laws, so caring for it means caring for society, and the phenomenon has spread. Domestic violence in human societies, due to poor social and moral issues, is one of the ugliest and most dangerous types of violence due to the deprivation of rights and loss of personalities that it causes, despite the absence of anything deterring this type of violence. However, Islamic and positive legislation prohibited it, criminalized it, and developed special methods to prevent its spread. And deterring anyone who tempts himself to practice it, regardless of his status.